Illegal Nickel Mining in Protected Forests: Challenges in Whistleblower and Justice Collaborator Protection in Indonesia - Utari, Indah Sri; Maskur, Muhammad Azil; Sumardiana, Benny; Ramada, Diandra Preludio; Alias, Nizamuddin (Universitas Negeri Semarang, 2025)
The systematic destruction of Indonesia’s Protected Forests—particularly in Southeast and Central Sulawesi—driven by illegal nickel mining operations poses an acute challenge to environmental rule of law. Utilizing data from recent cases (2023–2025) involving large-scale violations, such as those reported in the Mandiodo Block, this article critically assesses the effectiveness of existing legal mechanisms in protecting and utilizing key informants: the Corporate Whistleblower (WB) and the Justice Collaborator (JC). The analysis finds a significant gap between the legal mandate for protection and its implementation. Although Law No. 32/2009 (PPLH Law) guarantees identity confidentiality (Article 112), its utility is undermined by evidence of frequent retaliation against WBs—including job termination and counter-criminalization—by powerful corporate entities implicated in illegal nickel activities. Furthermore, the application of Law No. 31/2014 (LPSK Law) to grant JC status is often hindered by the reluctance of the judiciary to offer substantial sentencing concessions for environmental crimes, unlike in corruption cases. This reluctance limits the incentive for internal perpetrators to expose the Beneficial Owners who orchestrate the destruction of protected forest areas (e.g., the reported illegal clearing of hundreds of hectares for nickel ore extraction). This study concludes that the failure to establish robust, integrated legal immunity and sufficient sentencing differentiation for WBs and JCs transforms these protective instruments from effective crime-fighting tools into mere theoretical provisions. To successfully dismantle the complex, high-value chain of illegal nickel mining, the article recommends establishing a Specialized Penal Policy that standardizes the granting of JC status in environmental crimes, ensuring maximum physical and professional protection by the Witness and Victim Protection Agency (LPSK), and mandating its consideration for reduced sentencing to effectively breach the corporate veil.